2008
DOI: 10.3342/ceo.2008.1.1.46
|View full text |Cite
|
Sign up to set email alerts
|

Non-Functional Parathyroid Adenoma Presenting as a Massive Cervical Hematoma: A Case Report

Abstract: Parathyroid adenoma usually manifests with symptoms related to hypercalcemia, such as urinary stone and bone fracture. It may also present with asymptomatic hypercalcemia. However, spontaneous cervical hematoma may occur very rarely as a result of extracapsular hemorrhage of a cervical parathyroid adenoma causing acute painful cervical swelling, bruising, dyspnea, hoarseness and dysphagia. We report a 44-year-old woman who manifested as a spontaneous cervical hematoma without any clinical evidence of hyperpara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 11 publications
(18 reference statements)
0
8
0
Order By: Relevance
“…Scintigraphy is less widely used and in cases where the parathyroid sestamibi scan has been available, interestingly, the majority have not shown increased uptake in the area of concern. (2) (3) (6) (7). In our case, scintigraphy was a useful adjunct to confirming the diagnosis of parathyroid adenoma as there was a clear area of increased uptake.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Scintigraphy is less widely used and in cases where the parathyroid sestamibi scan has been available, interestingly, the majority have not shown increased uptake in the area of concern. (2) (3) (6) (7). In our case, scintigraphy was a useful adjunct to confirming the diagnosis of parathyroid adenoma as there was a clear area of increased uptake.…”
Section: Discussionmentioning
confidence: 54%
“…Shim et al . (7), however, reports a non-functional adenoma which could be explained by either tissue necrosis secondary to cystic degeneration or pressure from the haematoma compressing surrounding blood flow.…”
Section: Discussionmentioning
confidence: 99%
“…Second, PTH may be secreted into the lumen of the cyst instead of the bloodstream. Third, the pressure caused by the hematoma may interfere with blood flow around the adenoma [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, some patients are asymptomatic and present with normal serum levels of PTH and calcium. [3][4][5]7) Because of its rarity, a spontaneous rupture of a parathyroid adenoma is difficult to detect in patients who lack a diagnosis of adenoma, hyperplasia or pathologies of the parathyroid glands. The first case 1) was diagnosed by autopsy.…”
Section: Discussionmentioning
confidence: 99%
“…Over the last 80 years, approximately 20 cases of acute hemorrhage resulting from the spontaneous rupture of the parathyroid glands have been reported in the English literature. A previous study reported that the causes of these hemorrhages include parathyroid glands that are enlarged by adenomas, [1][2][3][4][5][6][7][8][9] primary or secondary hyperplasia, [10][11][12] cysts [13][14][15] and carcinomas. 16) Some authors report that blood supplies may occasionally fail to meet the increased demands caused by these lesions.…”
Section: Discussionmentioning
confidence: 99%